Does quality of care in hip fracture vary by day of admission? - Farrow, Luke (Arch Osteoporos, 2020)
SUMMARY: This study investigates if the day of the week a person is admitted with a hip fracture influences the quality of care they receive. We found those admitted Thursday and Friday were likely to obtain poorer postoperative care, indicating a need to optimize services ensuring equality for all. PURPOSE: We sought to investigate how the day of admission affects the quality of care provided to hip fracture patients according to national standards (The Scottish Standards of Care for Hip Fracture Patients [SSCHFP]). METHODS: Retrospective analysis of national cohort data. Data were collected by the Scottish Hip Fracture Audit (SHFA) local audit co-ordinators (LACs) at participating Scottish hospitals on behalf of NHS Scotland and the Scottish Government. Adherence to the SSCHFP included assessment of both individual and cumulative standard attainment as a marker for quality of patient care. RESULTS: From January 2014 to April 2018, 15,351 admissions for hip fracture were recorded. Compared with Monday admission (reference day), patients admitted on a Thursday or Friday had a significantly lower likelihood of achieving the postoperative standards of prompt mobilization (OR 1.77; p < 0.001 & OR 1.48; p < 0.001, respectively); prompt physiotherapy assessment (OR 8.61; p < 0.001 & OR 3.47; p < 0.001, respectively); and prompt comprehensive geriatric assessment (OR 1.88; p < 0.001 & OR 1.41; p < 0.001, respectively). Patients admitted on a Friday or Saturday were less likely to receive the preoperative standards of no delay prior to theatre (OR 1.24; p = 0.001 & OR 1.23; p = 0.002, respectively) and avoidance of repeat fasting (OR 1.22; p = 0.009 & OR 1.22; p = 0.01, respectively). CONCLUSION: Patients admitted on Thursday or Friday were significantly more likely to not receive postoperative care standards than patients admitted on the reference day (Monday). This appears to be related to inequalities in service provision for Saturday and Sunday compared with the rest of the week.